Spirituality and Severity of Menopausal Symptoms in a Sample of Religious Women - Steffen, Patrick R. (Journal of religion and health, 2011)
Menopause represents an important life change, particularly for religious women whose identity is significantly related to family. Two competing hypotheses are examined: one, because religious women have their identity focused on family and child rearing, spirituality will be related to increased menopausal symptoms because menopause represents a loss of identity and purpose; and two, because spirituality can provide strength and comfort during difficult times, it will, therefore, be related to decreased menopausal symptoms. To test these competing hypotheses, questionnaires were administered to 218 women (average age 55, 35% premenopausal, 26% peri-menopausal, 39% postmenopausal) who were members of the Church of Jesus Christ of Latter Day Saints. Regression analyses indicated that higher levels of spiritual strength were related to decreased levels of reported menopausal symptoms. Spiritual strength was also related to increased benefit finding during menopause, decreased concern with body appearance, and increased use of adaptive coping strategies. We conclude that finding strength in spirituality may help religious women cope better with the life changes associated with menopause.